Digitalisasi Proses Transaksi Dengan Perancangan Sistem Informasi Aplikasi Smart Cashier Pada Umkm Pisang Tanduk Goreng (Piston) - Azizie, Dicky Nur; Nasution, Syarifuddin (Jurnal Global Ilmiah, 2025)
The rapid development of information technology has driven significant changes in business processes, including in the Micro, Small and Medium Enterprises (MSMEs) sector. MSMEs are required to adapt to digitalization, especially in terms of operational efficiency and transaction recording. This study focuses on Pisang Antuk Goreng (PISTON) MSMEs that are still recording transactions manually, so they are at risk of fraud and lack of consumer appeal. The purpose of this research is to identify information system needs, design an AppSheet-based digital cashier application, and implement features such as automatic receipt printing, sending proof of transaction via email, and barcode scanning integration for customer member systems. The methodology used is the Waterfall method for system development and UML (Unified Modeling Language) for system modeling, as well as testing using the Black Box method to test the application function according to specifications. The development results show that the Smart Cashier application is able to record transactions in real-time, minimize the potential for fraud through digital receipt automation, and increase customer loyalty through the barcode member system. The conclusion of this study is that the application of the AppSheet-based Smart Cashier application in PISTON MSMEs can increase productivity, recording transparency, and competitiveness in the digitalization era.